O Estado de Direito e o pagamento das condenações judiciais pecuniárias: uma análise comparada entre o modelo jurídico brasileiro e o colombiano - Osório, Angie Mercedes Serrato (2022)
The payment of the monetary obligations of the State arising from court decisions are the only expenses that must be included in the budget without provision, and in relation to which there is no freedom as to whether or not to incur them. The disrespect, by the treasury authorities, of the creditor's rights, challenges Montesquieu's theory of separation of powers and denaturalizes the very image of the Rule of Law. In this context, the research, bibliographical and documentary, concerns the system of judicial precatories and is concerned with the improvement of this procedure so that it becomes a true regime of forced execution against the Administration and not a simple theoretical hypothesis. For this, through a comparative approach between the Brazilian and Colombian jurisdiction systems, the rules of execution for certain amount against the Public Treasury, both in terms of constitutional, legislative and jurisprudential descriptions, and in budgetary issues, were analyzed, seeking the verification of the effectiveness, or inefficiency, of them in the face of the protection of the existing interests, namely: the satisfaction of the citizen-creditor's rights and the preservation of the public patrimony. The purpose of the comparative study is not to transplant a foreign procedural remedy, but to learn from successful cases of the Colombian Constitutional Court in executive proceedings before the Executive Branch. As an original contribution to the legal doctrine in the country, it was presented as a proposal to improve the effectiveness of judicial decisions that impose a payment obligation on the State, among others, the reformulation of the current context of execution, even offering paradigms that go beyond the limits of the unseizability of dominical assets and public funds.